Epigenetics applied to child and adolescent mental health: Progress, challenges and opportunities - Charlotte A. M. Cecil; Alexander Neumann; Esther Walton (Wiley, 2023)
Abstract Background Epigenetic processes are fast emerging as a promising molecular system in the search for both biomarkers and mechanisms underlying human health and disease risk, including psychopathology. Methods In this review, we discuss the application of epigenetics (specifically DNA methylation) to research in child and adolescent mental health, with a focus on the use of developmentally sensitive datasets, such as prospective, population‐based cohorts. We look back at lessons learned to date, highlight current developments in the field and areas of priority for future research. We also reflect on why epigenetic research on child and adolescent mental health currently lags behind other areas of epigenetic research and what we can do to overcome existing barriers. Results To move the field forward, we advocate for the need of large‐scale, harmonized, collaborative efforts that explicitly account for the time‐varying nature of epigenetic and mental health data across development. Conclusion We conclude with a perspective on what the future may hold in terms of translational applications as more robust signals emerge from epigenetic research on child and adolescent mental health.